Managing rainwater, improving livelihoods: assessing impacts using a Rainwater–Livelihoods–Poverty Index (RLPI) - Getnet, Kindie; Kefyalew, G. (Cambridge University Press, 2013)
Assessing and empirically measuring the development impact of rainwater management innovations to inform related decisions remains conceptually and methodologically difficult. Whether it is empirically more appropriate to assess and measure the impact pathways than the impact per se remains an important methodological issue. This paper proposes a Rainwater–Livelihoods–Poverty Index (RLPI) as a comprehensive and participatory impact pathway assessment technique with measurable indicators recapitulating the sustainable livelihoods framework. The methodological contributions to rainwater impact assessment are two-fold. First, the RLPI explicitly incorporates intermediate processes and impact pathways as important factors affecting the development impacts of rainwater-related interventions. Second, the RLPI combines quantitative and qualitative household response data into a single yet meaningful quantitative impact indicator. This makes the methodology participatory, allowing farmers engagement to use their knowledge (as local expert observers) in informing rainwater management decisions. The methodology is empirically tested in Diga district (western Ethiopia) and validated using expert opinions.